PERBEDAAN PRESTASI AKADEMIK ANTARA LAKI-LAKI DAN PEREMPUAN STUDI DI WILAYAH YOGYAKARTA - Sartini Nuryoto (Faculty of Psychology, Universitas Gadjah Mada, 1998)
The aim of the study is to find out the difference of academic achievement based on gender. The result shows that there is significantly difference on academic achievement between male and female in general. Female academic achievement shows greater score than male. For further discussion, Female in elementary school, senior high school, diploma and also undergraduate degree has greater score than male. Meanwhile, in junior high school, there is no difference between male and female in their academic achievement.